Inactive hospital based cancer registries in eastern India exploring challenges and pathways to sustainability a qualitative study - Shubharanjan Jena; Venkatarao Epari; Krushna Chandra Sahoo; Sunil Agrawala; Raghul Durairaj (Discover Public Health)
Abstract Background Cancer poses a significant global public health challenge, with India experiencing a growing burden. Hospital-based cancer registries (HBCRs) are crucial for effective cancer surveillance and control; however, many HBCRs become inactive over time. Inactive HBCRs in this study are defined as registries that ceased cancer case data collection and reporting for at least one year due to operational or institutional challenges. This study explores multi-stakeholder perspectives on the challenges faced by HBCRs and suggests strategies for their sustainability in India. Methods A qualitative phenomenological approach was adopted, with in-depth interviews of oncologists, data managers, and medical social workers from four inactive HBCRs in Eastern India selected via convenience sampling. Within these sites, purposive sampling ensured diverse stakeholder perspectives in cancer care and registry management. Results The study identified multiple barriers to sustainability, including structural (limited resources, inadequate staffing), technological (lack of digital infrastructure), and organizational (low institutional priority, competing clinical workloads) factors. Conclusion Recommendations to address these challenges include standardizing legislation, enhancing digital infrastructure, and fostering stakeholder collaboration. Strengthening HBCRs through capacity building, digital innovation, and sustained funding can enhance cancer data quality and ultimately improve cancer surveillance and patient outcomes in India.